EFFECT OF SALT (NaCl) AGAINST WILT DISEASE OF COTTON CAUSED BY VERTICILLIUM DAHLIAE KLEB. UNDER IN VITRO CONDITIONS - Serife Evrim ARICI; Oktay ERDOGAN; Ziynet Nurcin TUNCEL (Journal of Animal and Plant Sciences, 2023)
Verticillium wilt disease causes economic yield losses in cotton growing areas in the world. In addition, an increase in salinity is observed in the soils of our country due to improper agricultural practices. This present study was carried out to find out the efficiency of NaCl with Verticillium dahliae Kleb. for two cotton cultivars following Completely Randomized Design (CRD). In this study, cotton cultivars (Gossypium hirsutum L.) of Nazilli 84 and Gloria were cultured in MS medium (40 ml per all magenta) containing 3 mycelial disc of Verticillium dahliae (0.5 mm) and different NaCL concentrations (0, 25, 50, 100, 150 mM) under in vitro conditions. The lowest disease severity value was found in the cv. Nazilli 84 in 150 mM NaCl + Verticillium dahliae application (48%), and in 100 mm NaCl + Verticillium dahliae application (50%) in cv. Gloria. In control plants, the disease severity was found to be 83% for cv. Nazilli 84 and 62% for cv. Gloria. Different results regarding plant height and leaf count were obtained with NaCl + Verticillium dahliae in cvs. Nazilli 84 and Gloria. Only with salt application, while the tallest plant height was determined to be 3.92 cm for cv. Nazilli 84 at 100 mM NaCl application, cv. Gloria was adversely affected by this application and plant height was measured at 1.83 cm determined. In conclusion, NaCl causes inhibition of V dahliae in both the cultivars of cotton at particular concentration. The analysis of variance for all the parameters (Plant height and number of leaves) were found to be significant at P≤ 0.05. These results show that salinity-tolerant cotton plants can increase their tolerance to V. dahliae infection. V dahliae disease can be suppressed by applying the NaCl concentration in the soil at appropriate doses depending on the cotton cultivars.
Keywords: Verticillium dahliae Kleb.; NaCl; disease severity; plant height; number of leaves; cotton